Asia's orthographic dilemma - Hannas, Wm. C., 1946- (University of Hawaiì Press, 1997)
With the advent of computers and the rise of East Asian economies, the complicated character-based writing systems of East Asia have reached a stage of crisis that may be described as truly millennial in scope and implications. In what is perhaps the most wide-ranging critique of the sinographic script ever written, William C. Hannas assesses the usefulness of Chinese character-based writing in East Asia today.